Crusading for Evidence-Based Actions. Galileo’s Middle Finger: Heretics, Activists, and the Search for Justice in Science by Alice Dreger - Bauer, Henry (Journal of Scientific Exploration, 2015)
<!--[if gte mso 9]> 14.00 <![endif]--> Progress, wrote George Bernard Shaw, depends on the unreasonable person,1 one who transgresses society’s dogmas and taboos. Alice Dreger is such an unreasonable one, and she has contributed mightily to tangible progress toward treating human beings as individuals, medically and socially; in particular those human beings who do not fall readily, physically or emotionally, into distinct categories of “male” or “female”. This book is Dreger’s personal, passionate, colloquial account of three crusades. Few readers will fail to learn a great deal about the varieties of human sexual identity, and few will fail to be engrossed by these true tales of good deeds and bad deeds, of admirable actors and not-so-admirable ones. Dreger — studying history and philosophy of science and believing herself to be a feminist — wanted a PhD topic relating to issues of gender.2 Mentors suggested hermaphroditism. That led to contact and collaboration with activists in the “intersex” community, individuals born with mixtures of the organs and tissues that physically define “male” and “female”. Standard medical practice — into the late 1990s — was for pediatric surgeons to decide whether a given baby should be male or female and to perform “corrective” surgery as a matter of course, typically without consulting the parents. Dreger and her collaborators achieved a great deal toward changing medical practices so that parents make the early decisions, preferably (p. 49) to do nothing until the affected individuals are of an age to make their own individual decisions. This crusade brought considerable publicity, which led to Dreger’s being urged to look into the vicious attacks that had been made on Michael Bailey, an academic psychologist who expounded the views of Ray Blanchard, that there are two distinct categories of men who seek male-to-female sex change. One group comprises gay men, erotically attracted to men; the other are “autogynephiliac” men who experience erotic attraction to the idea of being female without necessarily being attracted erotically to men. The concept of autogynephilia had offended several trans-women to the degree that they waged a campaign to blacken Bailey’s reputation, using means that included public attacks on his family. The intellectual passion driving Dreger’s work is that justice must be evidence-based: evidence and not ideology must be decisive. Good intentions don’t guarantee good actions or outcomes, while those whose actions are damaging are not necessarily evil people (p. 275). The lessons of history may be clear, but historians are not listened to (p. 276). Dreger’s analysis of what happened to Michael Bailey (Dreger 2008) illustrates the scrupulous seeking and collation of evidence that characterizes first-rate historical work.3 Dreger was shocked to find that the anti-Bailey activists were wrong on salient facts, even as they claimed moral authority based on personal experience and feelings — in other words, they were politically correct. As Galileo’s Middle Finger insists over and again, views of what is ethical and moral must accord with the facts; political correctness, in other words, is simply wrong and often irrational.4 Dreger’s analysis of the willful destruction of Bailey’s academic career on false grounds brought Bailey at least some after-the-fact comfort. It also brought Dreger the invitation to look into a similar scandal. Once more she contributed to a belated recognition that the anthropologist Napoleon Chagnon had been vilified and hounded in a campaign of ideologically based and factually false accusations (Dreger 2011). Dreger’s third crusade over human sexual identity concerned the disorder of congenital adrenal hyperplasia (CAH), which involves excessive production of androgens that can lead to ambiguous genitalia and quite serious risks to health in genetic females. CAH is genetically recessive, affecting female babies who inherit the pertinent mutation from both parents: there is 1 chance in 4 that a girl will suffer the disorder if both parents carry this genetic marker<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->